1985
DOI: 10.1530/jrf.0.0740167
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin-induced abnormalities in sheep oocytes after superovulation

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
1
3

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(83 citation statements)
references
References 14 publications
5
74
1
3
Order By: Relevance
“…Although some evidence has been observed of an alteration in oocyte activation and in patterns of oocyte protein synthesis, or follicular steroidogenesis capacity [24] and ovulation time [39], the reason why FSH alone produces better quality embryos than eCG is not fully understood. Armstrong [2] has suggested that acceleration of follicle development during superovulatory treatment can occur before complete growth to allow completion of maturational process of cytoplasmic oocyte and granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some evidence has been observed of an alteration in oocyte activation and in patterns of oocyte protein synthesis, or follicular steroidogenesis capacity [24] and ovulation time [39], the reason why FSH alone produces better quality embryos than eCG is not fully understood. Armstrong [2] has suggested that acceleration of follicle development during superovulatory treatment can occur before complete growth to allow completion of maturational process of cytoplasmic oocyte and granulosa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Driancourt and Fry [12] have shown that eCG could determine variations in the morphological features of the preovulatory follicles, altering the size and number of granulosa cells which play an essential role in the transport of regulatory signals and metabolic substrates to full oocyte maturation. This could result in alterations and deficiencies of patterns of protein synthesis during meiotic progression compromising the subsequent potential capacity of oocytes derived from treated sheep to embryo development [24].…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al [19] observed a biphasic increase of E2 secretion in superovulated ewes when pFSH and eCG were given on Day -2 and Day -1, respectively before sponge removal. The higher estrogen levels from persistent large follicles have been considered to enhance ova transport through the oviducts and become detrimental to fertilization and the development of embryos [7,24,25]. It has been reported that an administration of exogeneous estrogen shortly after ovulation induced premature luteal regression in cows [26] and in rhesus monkeys [27].…”
Section: Discussionmentioning
confidence: 99%
“…ultiple injections of follicle-stimulating hormone (FSH) or a single injection of equine lation, but its relatively high level of estradiol-17β (E2) remaining in the unovulatory follicles and in the blood has imparied oocyte maturation, time of ovulation and the yield of fertilized ova [6,7].…”
mentioning
confidence: 99%
“…Pregnant mare serum gonadotrophin (PMSG) [6], pituitary extracts of different origin [28,69,96] and human menopausal gonadotrophin [92] are commonly used for superovulation in sheep. The biological properties of the gonadotrophins used for superovulation have been described in detail elsewhere [13]; for review see [45] [67] or later, during early embryonic development as a result of unbalanced hormonal profiles [3,51] [66], association of these two gonadotrophins [91], single versus multiple injections [30,64], or inclusion of GnRH or growth hormone in the treatments [36,111].…”
Section: Superovulationmentioning
confidence: 99%